Italian Study on Buckwheat Allergy: Prevalence and Clinical Features of Buckwheat-Sensitized Patients in Italy. (July 2013) - Badiu, I.; Olivieri, E.; Montagni, M.; Guida, G.; Mietta, S.; Pizzimenti, S.; Caminati, M.; Yacoub, M.R.; Tombetti, E.; Preziosi, D.; Quecchia, C.; Minetti, S.; et al.
Buckwheat allergy is considered a rare food allergy outside of Asia. In Europe, buckwheat has been described mainly as a hidden allergen. Data on the prevalence of buckwheat hypersensitivity in non-Asian countries is very poor. The aim of this multicenter study was to evaluate the prevalence of buckwheat sensitization and its association with other sensitizations among patients referred to allergy clinics in different geographic areas of Italy. All patients referred to 18 Italian allergy clinics from February through April 2011 were included in the study and evaluated for sensitization to buckwheat and other allergens depending on their clinical history. A total of 1, 954 patients were included in the study and 61.3% of them were atopic. Mean prevalence of buckwheat sensitization was 3.6% with significant difference between Northern (4.5%), Central (2.2%) and Southern (2.8%) regions. This is, to our knowledge, the largest epidemiological survey on buckwheat allergy reported outside of Asia. Buckwheat is an emerging allergen in Italy, being more frequently associated to sensitization in Northern regions.